The Wilderness and Wonderfulness of Women Health - Awi, Idi (UNIMAS Publisher, 2021)
This book is aimed to discuss recent progress and highlight the current challenges and controversies of Women’s Health in the 21st century that need to be addressed. Women’s health is closely related to reproductive health. It has many different aspects which can be addressed by the clinician, the public health specialist and the gender advocate, among others. The emphasis on the discussion is placed on the following issues; genetic counselling, caesarean section as opposed to normal delivery, adolescent pregnancy, assisted reproductive techniques, gynaecological cancer and ageing women. Elements of ethics and medicolegal aspects of managing women are also deliberated in this book. The general role of the Obstetrician and Gynaecologist (O&G) is to care for pregnant mothers and deliver an alive healthy baby, hence, promoting healthy population growth that would contribute to the countries’ development. A childless couple who longs to have a child, now can conceive and have a healthy baby, thanks to the advanced of assisted reproductive techniques being facilitated by the O&G specialists. Rapid developments and revolutionized in the medical field in the last century, the medical practice is at crossroads facing many ethical and legal challenges in the practice of the profession, whereby the obstetrics and gynaecology field are not spared either.